2014
DOI: 10.1371/journal.pone.0097723
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Velocity of PM2.5 in the Winter and Spring above Deciduous and Coniferous Forests in Beijing, China

Abstract: To estimate the deposition effect of PM2.5 (particle matter with aerodynamic diameter <2.5 µm) in forests in northern China, we used the gradient method to measure the deposition velocity of PM2.5 during the winter and spring above a deciduous forest in Olympic Forest Park and above a coniferous forest in Jiufeng National Forest Park. Six aerosol samplers were placed on two towers at each site at heights of 9, 12 and 15 m above the ground surface. The sample filters were exchanged every four hours at 6∶00 AM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
0
31
1
Order By: Relevance
“…According to previous measurements at the site, the leaf area index (LAI) at the Jiufeng National Forest Park site was 3.8 in spring, and was 1.8 at the Olympic Forest Park site [18].…”
Section: Experimental Descriptionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to previous measurements at the site, the leaf area index (LAI) at the Jiufeng National Forest Park site was 3.8 in spring, and was 1.8 at the Olympic Forest Park site [18].…”
Section: Experimental Descriptionmentioning
confidence: 84%
“…According to previous measurements at the site, the leaf area index (LAI) at the Jiufeng National Forest Park site was 3.8 in spring, and was 1.8 at the Olympic Forest Park site [18]. in forest systems have been mainly conducted in Europe and the United States [8][9][10][11][12][13][14], as well as some Asian countries other than China [15][16][17].…”
Section: Experimental Descriptionmentioning
confidence: 97%
“…The studies showed that for Populus, when the wind speed is 3 m·s . Due to this study taking place in the same experimental area as that of Sun et al [57], we regard the deposition velocity of PM2.5 in this study as 0.9 ± 0.8 cm·s [55,58]; here we also adopted this value. With an increase in the particle size range of 0.1-10 μm, aerosol deposition velocities are greater [58].…”
Section: Urban Forest Effects Model: Air Particulate Removed By Treesmentioning
confidence: 99%
“…In Jing-Jin-Ji and Chengdu-Chongqing regions, however, the urbanization is characterized by few highly-developed metropolitans, resulting in relatively centralized pollution sources [61,62]. Under this condition, the heterogeneous landscape might be helpful for the PM 2.5 dispersion over the regions [26,27,63]. The AI also positively correlates to the PM 2.5 concentration in most regions, except for the Yangtze River Delta and Chang-Zhu-Tan urban agglomerations.…”
Section: Regional Scalementioning
confidence: 99%